Case Report: Testicular Pseudoaneurysm Rupture - Caroline Baber; Eshaan Daas; Michelle Mouri (Clinical Practice and Cases in Emergency Medicine)
Introduction: Gastroduodenal artery embolization is an increasingly common treatment method in patients with upper gastrointestinal (GI) bleeding who fail endoscopy or as a prophylactic procedure to help prevent further episodes. However, this new technique includes new risks including GI tract ischemia and risks associated with endovascular access such as hematoma formation, pseudoaneurysm development, and arterial dissection. Case Report: We discuss a case of 51-year-old male with recurrent upper GI bleeding who presented to the emergency department for scrotal swelling following the prophylactic embolization of his gastroduodenal artery. He was subsequently found to have a ruptured testicular artery pseudoaneurysm resulting in hemorrhagic shock, which required massive transfusion protocol and vascular repair. Conclusion: While endovascular access is relatively safe, patients can develop severe complications such as pseudoaneurysm development and subsequent rupture that may not be obviously apparent on physical exam. Because of this, clinicians must have a high index of suspicion for arterial injury, and risk stratification should be used when selecting appropriate candidates for prophylactic procedures.